Meningitis in the Kaiser Permanente Northern California (KPNC) Pediatric Population 2012 through 2016 and Its Association with Prior Traumatic Brain Injury (TBI). (4th October 2017) - Chu, Victoria; Carpenter, Diane; Postlethwaite, Debbie; Harriman, Kathleen; Glaser, Carol
Abstract: Background: The incidence of meningitis, particularly bacterial meningitis, is decreasing due to widespread vaccine use with etiologies still due to relatively common organisms. However, risk factors for the development of meningitis are largely unknown. We describe the epidemiology of meningitis among the pediatric population of KPNC and assess the association between prior TBI and meningitis. Methods: We conducted a retrospective descriptive study among KPNC pediatric patients (1 month-18 years) between July 2012 - June 2016 with an ICD-9 meningitis diagnosis. Charts were reviewed to a.) verify and classify the meningitis diagnosis and b.) ascertain prior TBI history. Cases were classified as confirmed, probable, or possible based on clinical course, CSF culture, PCR, and CSF profile. The proportion of meningitis cases with a history of TBI was compared with the published rate of TBI in the general pediatric population. Results: Of 266 cases reviewed, 146 cases were verified as meningitis with 19 confirmed/probable bacterial [( S. pneumoniae (7), E. coli (3), S . A galactiae (3), N. meningitidis (2), S . A ureus (1), and not otherwise specified (3)] and 50 confirmed/probable viral [(enterovirus (44), HSV2 (4), HSV1 (1), and WNV (1)] etiologies. An additional 77 possible cases included primarily viral etiologies (65) and a minority of possible bacterial (6) or infection-related inflammatory (6) etiologies. 120 were excluded. The overall meningitis and confirmed bacterial meningitis estimated incidence rate was 17.9 per 100, 000 and 2.7 per 100, 000, respectively. Twenty meningitis cases (13.7%) had a history of TBI (all of which were concussions) compared with the concussion rate in the general pediatric population reported by AL Zhang et al of 0.7% ( P < 0.001). Conclusion: Our results are consistent with recent studies showing a decline in bacterial meningitis. Enteroviral meningitis remains the leading cause of identified etiologies. However, in a sizable proportion of cases there was no specific pathogen identified. An increased risk of developing meningitis may be associated with TBIs. Disclosures: All authors: No reported disclosures.